2023
DOI: 10.1136/bcr-2022-253172
|View full text |Cite
|
Sign up to set email alerts
|

Scrub typhus due to vertical transmission in a neonate: rare presentation of a common tropical infection

Abstract: Vertical transmission as a route of infection has been well reported in many viral infections. Scrub typhus is a zoonotic disease transmitted by ticks which has had a resurgence in recent times in several tropical countries. It affects all age groups including neonates. Reports of neonates affected with scrub typhus are few, and vertical transmission is rare. We report a case, where a newborn was symptomatic with signs of infection within the first 72 hours of life and Orientia tsutsugamushi, the causative org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The modes of transmission in neonates may include mite-borne transmission, trans-placental transmission, and perinatal blood-borne transmission ( 16 ). A brief literature review reveals 22 reported cases of neonatal scrub typhus ( 8 ). Most cases were attributed to mite-borne transmission, while a few were associated with trans-placental transmission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The modes of transmission in neonates may include mite-borne transmission, trans-placental transmission, and perinatal blood-borne transmission ( 16 ). A brief literature review reveals 22 reported cases of neonatal scrub typhus ( 8 ). Most cases were attributed to mite-borne transmission, while a few were associated with trans-placental transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Among these diagnostic methods, molecular-based methods such as PCR and NGS exhibit higher specificity and sensitivity ( 19 ). However, during the acute stage of neonatal scrub typhus, the results of the serological test often turn out to be negative, which can lead to misdiagnosis and a high risk of complications and mortality ( 8 ). Therefore, it is crucial to consider scrub typhus as a potential diagnosis in children and initiate prompt treatment ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation